Hematologic, Blood Gas, Cardiac Biomarkers and Serum Biochemical Parameters in Calves with Atresia Coli and Theirs Relationship with Prognosis - Coskun, Alparslan; Aydogdu, Ugur; Altan, Semih; Erol, Muharrem; Erol, Hanifi; Guzelbektes, Hasan; Sen, Ismail (Acta Scientiae Veterinariae, 2017)
Background: Atresia coli is an intestinal anomaly. Generally, absence of defecation in calves less than 10 days old, diminishing appetite, progressing abdominal distention and time-developing depression are reported in atresia coli. Although a calf consumes its milk normally in first days, loss of appetite develops over time. Occasional minor pain indications are observed. The objective of this study was to evaluate of hematologic, blood gases, cardiac biomarkers and serum biochemical parameters before operation in calves with atresia coli, and to investigate relationship with prognosis of these parameters. Materials, Methods & Results: Thirty calves with atresia coli and 6 healthy calves for control were used as material. Poor suction reflex, anorexia, dehydration, abdomen-kicking, frequent leg movement, abdominal distension and depression were observed in calves brought to the clinic. Some calves presented swashing sound depending on content of intestines when abdomen was shaken. Intestine atresia was diagnosed by history and clinical examination. After clinical examination, operation was performed. All calves were observed during 10 days after operation. Fifteen of 30 calves died during 10 days after operation. The blood lactate, WBC, LDH and CK-MB levels in non-surviving calves with atresia coli were significantly higher compared to control calves. The venous blood pH level was significantly lower in non-surviving calves compared to surviving calves. In addition, when compared to the control group, the blood pCO2 level was significantly higher in non-surviving and surviving calves with atresia coli while the pO2 and O2 saturation levels were significantly lower. Discussion: In calves with intestinal atresia, hematologic parameters are normal in first 48 h of disease. However, leukocytosis and shift to the left have been reported over time. However, leukocytosis due to peritonitis, bacterial overgrowth, etc. have been reported over time. It was seen that leukocyte numbers of non-surviving calves with atresia coli in this study were significantly higher, but leucocyte increase in surviving calves was seen to be statistically insignificant. Leukocyte increased in non-surviving calves with atresia may be associated with excessive bacterial reproduction and peritonitis. Blood lactate level is a commonly used marker for severity of disease in humans and lactate has a prognostic value in adult horses with colic and foals with critical disease. In this study, lactate level in non-surviving calves with atresia coli was significantly higher with respect to surviving calves and control calves. In this result, lactate can be evaluated as a prognostic indicator in calves with atresia coli. Creatine kinase-MB fraction and troponins are used in determination of cardiac damage in veterinary medicine. The fact that serum blood cTnI and CK-MB levels of non-surviving calves with intestinal atresia in this study were higher than surviving calves with atresia coli and control calves suggested that endotoxemia related cardiac damage may have developed. Surgical operation is necessary in the treatment of intestinal atresia. It was determined that the importance of calves age and colon integrity during time of surgical operation in survival of calves with atresia coli. The studies showed that survival rate in surgical operation conducted on calves under 3 days old was higher than calves over 5 day-old. Average of age of non-surviving calves with atresia coli in this study (4.67 ± 1.23 days) was higher than average of age of surviving calves with atresia coli (3.27 ± 0.51 days). It was also observed in our study that elapsed time affected prognosis of calves negatively. Thus, performing surgical operations as soon as possible may raise survival rate of calves with intestinal atresia as stated in previous studies.